Radar Altimetry as a Robust Tool for Monitoring the Active Lava Lake at Erebus Volcano, Antarctica. Issue 17 (2nd September 2018) - Peters, N. J.; Oppenheimer, C.; Brennan, P.; Lok, L. B.; Ash, M.; Kyle, P.
Abstract: The level of lava within a volcanic conduit reflects the overpressure within a connected magma reservoir. Continuous monitoring of lava level can therefore provide critical insights into volcanic processes and aid hazard assessment. However, accurate measurements of lava level are not easy to make, partly owing to the often dense fumes that hinder optical techniques. Here we present the first radar instrument designed for the purpose of monitoring lava level and report on its successful operation at Erebus volcano, Antarctica. We describe the hardware and data‐processing steps followed to extract a time series of lava lake level, demonstrating that we can readily resolve ∼1 m cyclic variations in lake level that have previously been recognized at Erebus volcano. The performance of the radar (continuous, automated data collection in temperatures of around −30 °C) indicates the suitability of this approach for sustained automated measurements at Erebus and other volcanoes with lava lakes. Plain Language Summary: Active lava lakes are the exposed top of a volcano's magmatic plumbing system. Although only found at a handful of volcanoes worldwide, they are important because they allow direct measurements of magmatic processes which at other volcanoes occur underground and out of sight. The surface level of these lakes is an important parameter to monitor, because it reflects pressure changes in the underlying magmatic system. However, it is remarkably difficult to measure, because their surface is often obscured by the volcanic gases emanating from the lava. We have developed the first radar instrument for monitoring lava lake level, which can effectively see through the volcanic gases, providing an accurate measure of lake level regardless of visibility. The radar was deployed at Erebus volcano, Antarctica and successfully recorded the longest‐duration measurements of its lava lake's surface level made to date. The radar was able to clearly resolve the meter‐scale variations in lake level that have previously been documented at Erebus. Our study shows that radar is a promising solution for long‐duration studies of lava lakes, and we are working on refining our design into an operational tool to support volcanological studies and hazard assessment at other volcanoes around the world. Key Points: The level of active lava lakes is a key parameter in their study but surprisingly hard to measure Eredar is a new radar system for monitoring surface level of active lava lakes At Erebus volcano it collected the longest continuous time series of lake level to date